Pertumbuhan dan Hasil Tanaman Sawi Pagoda (Brassica narinosa L.) Akibat Pemberian Pupuk Organik Cair Kascing, Papua Nutrient dan MA-11 - Ivonne Fitria Mariay; Bayu Imam Segoro; Besse Amriati; Rizald Hussein (Agrotek, 2022)
This research was conducted at the screen house of the Faculty of Agriculture, University of Papua. The objective was to determine the best type of liquid organic fertilizer for the growth and yield of Pagoda mustard plants. Using a non-factorial randomized block design (RAK), with 4 treatments repeated 4 times, in order to obtain 16 trials. The treatments in this study included 1) Control, 2) Liquid organic fertilizer Kascing (10 ml), 3) Papua Nutrient liquid organic fertilizer (10 ml), 4) MA-11 liquid organic fertilizer (10 ml + 10 g granulated sugar). The results showed that the fertilizer treatment in Papua Nutrient showed a significant effect. This treatment gave the best results when compared to the Kascing fertilizer treatment and the MA-11 fertilizer treatment. The Papua Nutrient fertilizer treatment had a significant effect on plant height, leaf width, growth rate, leaf width increase rate, wet weight and root weight with the highest average.